Estimating the Value of Higher Education Financial Aid: Evidence from a Field Experiment - Belzil, Christian; Maurel, Arnaud; Sidibé, Modibo (Journal of Labor Economics, 2021)
Using data from a Canadian field experiment on financial barriers to higher education, we estimate the distribution of the value of financial aid for prospective students. We find that a considerable share of prospective students perceive significant credit constraints. Most individuals are willing to pay a sizable interest premium above the prevailing market rate for the option to take up a loan, with a median interest rate wedge equal to 6.8 percentage points for a $1,000 loan. The willingness to pay for financial aid is heterogeneous across students, with discount factors playing a key role in accounting for this variation.